SELECTION OF AN APPROPRIATE DISTRIBUTION CHANNEL FOR HIGH-VALUE STONE - Mikušová, Nikoleta; Tomková, Eva; Hrdý, David; Průša, Petr; Kampf, Rudolf (My University, 2018)
Selection of distribution channel type is an important decision of every manufacturing company and also for production engineering. Appropriate choice of distribution channel can save considerable costs while maintaining a high level of customer service. Determination of an appropriate strategy for the management of enterprise distribution channel. In this article, the selection of the type of distribution channel is proposed using ANP method to determine the strength of influence of input factors on the target set of potential options. Submitted model is very clear, understandable and according to the proposed methodology easy to implement, while also providing clear and understandable results during the selection of the type of distribution channel. The proposed model is primarily targeting for distribution of high-value stone which needs to decide which distribution strategy should be chosen or if to switch to another distribution strategy more suitable for the company needs.
Volba vhodného distribučním kanálem pro vysoce hodnotných STONE
Keywords: SELECTION; DISTRIBUTION CHANNEL; HIGH-VALUE STONE; Volba; distribuční kanál; pro; vysoce; hodnotné kameny